2011
DOI: 10.1159/000319049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Magnesium Sulfate Administration on Intestinal Blood Flow Velocity in Preterm Neonates

Abstract: Background: Antenatal MgSO4 administration is used extensively as a tocolytic agent and to treat preeclampsia. Various effects on the fetus and newborn have been reported, and MgSO4 has well-documented vasoactive effects. Objective: To determine if antenatal MgSO4 administration affects intestinal blood flow velocity in newborn preterm infants. Methods: Peak, mean and end-diastolic velocities in the superior mesenteric artery were measured on day 1 of life. Maternal medical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 77 publications
1
23
0
Order By: Relevance
“…One study suggested antenatal MgSO 4 treatment was associated with increased intestinal blood flow immediately after preterm birth (Havranek et al . ). The present finding that MgSO 4 increases peripheral perfusion indicates that it would be valuable to carefully assess whether the risk of NEC and renal impairment are affected by MgSO 4 exposure.…”
Section: Discussionmentioning
confidence: 97%
“…One study suggested antenatal MgSO 4 treatment was associated with increased intestinal blood flow immediately after preterm birth (Havranek et al . ). The present finding that MgSO 4 increases peripheral perfusion indicates that it would be valuable to carefully assess whether the risk of NEC and renal impairment are affected by MgSO 4 exposure.…”
Section: Discussionmentioning
confidence: 97%
“…MgSO 4 decreases intestinal peristalsis [13], can possibly alter mesenteric blood flow [14, 15], and is associated with feeding intolerance in neonates [16]. It also crosses the placenta freely with a linear relationship between maternal and neonatal levels [17-19].…”
Section: Discussionmentioning
confidence: 99%
“…Exposed preterm infants may be at risk for hypermagnesemia and its associated complications as well. Several studies implicate increased neonatal morbidities in the presence of high mMgC or iMgC, among them increased risk of death, high grade IVH, risk for intubation and patent ductus arteriosus . In view of the preceding risks, the American Academy of Pediatrics and the Neonatal Resuscitation Program supported by the American Heart Association listed MgSO4 among the maternally administered medications that may cause respiratory depression in newborns .…”
Section: Discussionmentioning
confidence: 99%